Development and psychometric evaluation of the self-assessment of psoriasis symptoms (SAPS) – clinical trial and the SAPS – real world patient-reported outcomes. (18th August 2017) - Armstrong, April W.; Banderas, Benjamin; Foley, Catherine; Stokes, Jonathan; Sundaram, Murali; Shields, Alan L.
Abstract: Objective: The Self-Assessment of Psoriasis Symptoms – Clinical Trials (SAPS-CT) and SAPS – Real World (SAPS-RW) were simultaneously created to assess the experience of plaque psoriasis in two unique contexts. Methods: Qualitative and quantitative research was conducted in four phases namely concept elicitation, questionnaire construction, content evaluation and psychometric evaluation. Results: Following concept elicitation, 18 concepts were selected to inform questionnaire construction of the SAPS-CT and SAPS-RW. To accommodate each context of use, the SAPS-CT asks respondents to rate the target symptom 'at its worst' in the 24 h prior to assessment, while the SAPS-RW asks respondents to rate the target symptom "on average" in the 7 days prior to assessment. Cognitive debriefing confirmed that patients could comprehend and provide meaningful responses to both versions and, after minor modifications, resulted in 11-item questionnaires administered in an observational study ( N  = 200). Results from the observational study informed further item reduction (SAPS-RW to six items and SAPS-CT to nine items) and demonstrated that scores from each were reliable (Cronbach's α > 0.90, test–retest intraclass correlation coefficient >0.70), construct valid and able to differentiate among clinically distinct groups. Conclusion: The SAPS-CT and SAPS-RW are content-valid PRO questionnaires capable of producing psychometrically sound scores when administered chronic to plaque psoriasis patients.